The INDDEX24 Dietary Assessment Platform Is As Accurate as Pen-and-Paper 24-Hour Dietary Recall When Compared to a Weighed Food Record Benchmark in Viet Nam. (7th June 2021) - Bell, Winnie; Coates, Jennifer; Bakun, Peter; Somé, Jérôme; Colaiezzi, Brooke; Do, Ha Phuong; Rogers, Beatrice
Abstract: Objectives: The study assessed the relative accuracy of INDDEX24, a computer-assisted personal interview (CAPI) approach to conducting a 24-hour dietary recall (24HR), compared to the pen-and-paper interview (PAPI) approach against a full-day observed weighed food record (WFR) in northern Viet Nam where the diet is diverse and complex. Methods: Women aged 18–49 from northern Viet Nam were randomly assigned to be interviewed with the CAPI or PAPI 24HR the day after other enumerators conducted a WFR. The Two One Sided T-test (TOST) assessed equivalence of each recall-benchmark method comparison using a 10% bound. A difference-in-differences approach compared the significance of differences between the CAPI vs. WFR and PAPI vs. WFR modalities. Nutrient intakes were logged to achieve a normal distribution. Results: Both the PAPI and the CAPI were statistically equivalent to the WFR across indicators of average total food items, total grams of intake, energy intake, all macro- and micronutrients tested (except Vitamin A for both CAPI and PAPI). The difference-in-difference analysis showed that the CAPI diverged significantly less than PAPI from the WFR for iron (0.9 v. −1.3 mg) and PAPI diverged less from the WFR than CAPI for protein (−3.7 v. 7.9 grams). There were no other statistically significant differences and, for both PAPI and CAPI, average deviations from the WFR were small. Individual-level comparisons showed 56% of PAPI and 59% of CAPI respondents were within +/−20% of the WFR intakes, while 26% of respondents in the PAPI group and 32% of the CAPI group had energy intakes by 24HR within +/- 10% of the WFR intakes. Conclusions: INDDEX24 was an accurate method for assessing food and nutrient intake among women of reproductive age in northern Viet Nam, when compared to a WFR. INDDEX24 performed at least as well as the PAPI 24HR modality across several different group and individual level measures for energy and nutrients of interest. Digital data collection platforms facilitate standardization of data collection and may reduce survey time and costs. Given these advantages, the INDDEX24 Dietary Assessment Platform should be considered for implementing high quality, individual-level, quantitative dietary surveys in low- and middle-income countries. Funding Sources: Bill and Melinda Gates Foundation.